Systematic Literature Review: Criminal Law Reform in Indonesia - Luturmas, Rinaldi Rifli Yulyans; Meisa, Dhea; Kadir, Syukron Abdul; Kamlasi, Elizabeth RD; Firmansyah, Ega Diki; Shabrian, Ghozi Alfarizki (PT FORMOSA CENDEKIA GLOBAL, 2024)
Technological developments have triggered the phenomenon of change in society. The law as a tool for enforcing justice also adapts along with the development of crime in society. Currently, Indonesia is entering a polemic between the old criminal law and the new criminal law, because the old criminal law is considered irrelevant and not in accordance with the rules of the Indonesian nation. This is reflected, coupled with the Republican government wanting legal instruments and systems that are completely independent from the previous system created by the Dutch. The purpose of this article is to examine criminal law reform in Indonesia, so that this can answer existing problem phenomena. The method used in this research is the Systematic Literature Review (SLR) method with a qualitative approach.